Development of Mental Health Application: Design Thinking Approach - Imam Hidayat, Adnan; Ghina , Astri (AFEBI Management and Business Review, 2025)
The growing demand for inclusive and accessible mental health services presents a global challenge, including in Indonesia. In response, Ibunda.id developed the WellMe application using the Design Thinking approach to understand user needs, design innovative solutions, and create an effective technology-based prototype. This study follows the five stages of Design Thinking: Empathize, define, ideate, prototype, and test. Customer Journey Mapping and Empathy Maps identified key challenges, including the absence of a mobile application, which limited user convenience: the define stage prioritized push notifications, educational content, and psychologist profiles with user reviews. Using 2x2 brainstorming, the ideation stage led to solutions such as multiplatform development with Flutter, video call integration, and interactive educational modules. Prototyping resulted in a mobile application tailored to user needs. Usability testing with the System Usability Scale (SUS) scored 81.5 ("excellent"), indicating high satisfaction. Desirability analysis highlighted appreciation for push notifications and personalized psychologist profiles. Viability showed strong engagement potential, with 100% of respondents favoring the app over the web platform. Feasibility analysis found 93.2% of developers endorsing Flutter for its efficiency and cost-effectiveness. This study contributes to design thinking literature on mental health applications. It provides a framework for user-centered technological innovations, supporting Ibunda.id in enhancing service accessibility and quality in Indonesia.